Client-Server Model Non-Stationary Behaviour Research at Near Self- Similar Query Stream Influence Under the Condition of Overloaded Terminal System - Jerjomins, R.; Petersons, E. (Elektronika ir Elektrotechnika, 2006)
A plenty of experimental research papers show that in modern computer and telecommunication networks traffic is self-similar. Traditional calculation methods of network switching and processing device parameters are based on the elementary query or packet streams. In a number of researches it is shown, that traditional approach lead to big mistakes in devices parameters definition. These conclusions have been made on the basis of devices stationary operating mode analysis. In the given work terminal-server system nonstationary operating mode at near to self-similar query stream influence is considered. Ill. 8, bibl. 5 (in English, summaries in English, Russian, Lithuanian).